Risk Assessment of Computer Network Security in Banks - Singha, Anjani Kumar (IJRDO -Journal of Computer Science Engineering, 2017)
The importance of computer system security of banks can never be exaggerated.Conducting risk assessment of computer system security of banks can increase safetymanagement and ensure normal operation. This paper firstly figures out risk assessmentindexes for computer system security of banks through literature review and survey.Secondly, it uses AHP to confirm the weight of indicators and establishes five securitylevels. According to the judgment of experts, it finally establishes the risk assessmentmodel for computer system security of banks.